Nilai Estetika dalam Komik Jepang Detektif Conan Seri 720: The Kappa’s Curse Karya Aoyama Gosho - Yulistiyanti Yulistiyanti (Universitas Stikubank (UNISBANK) Semarang, 2012)
Manga is Japanese comic which has been trend in Indonesia recently. This work has its own aesthetics values and they reveal the Japanese philosophy of life. Japanese applies zen budhisme in their life as well as Aoyama Gosho, Detective Conan author (mangaka). Wabi-sabi, the Japanese aesthethic values also teaches us how life goes. It teaches us using imperfectness, incompleteness, and impermanence to make us balance with the natural process. Realism applied by Gosho to depict his characters and it looks so real. Readers seem close to the condition which he describes. Detective story always makes tension for the readers. It also makes this manga interesting to read. Catharsis could be felt after finishing reading Detective Conan. Key words: Japanese comic, manga, mangaka, tension, realism, zen budhism, wabi-sabi